MANAJEMEN RISIKO PADA PT X MENGGUNAKAN METODE RBS DALAM PENYEDIAAN LAYANAN TELEKOMUNIKASI - Mayun, Gung (JUSS (Jurnal Sains dan Sistem Informasi), 2023)
The company PT X is a provider company that has been established since 1989. One of the keys to the success of PT X can survive until now is to make a transformation that aims to provide services to customers and increase company value. In the current conditions, the telecommunications industry in Indonesia requires a broad and explicit evaluation that emphasizes business risk. To overcome these risks, while recognizing the business development opportunities that accompany them, further guaranteeing the realization of the Company's various strategic plans and ensuring business continuity, PT X applies the ISO 31000 Risk Management ("ERM") framework as one of the pillars to support good corporate governance (Good Corporate Governance). The purpose of ERM is to embed the principles and practices of risk management into the development of strategies and day-to-day operational processes in a very practical way to add value to the Company. This paper discusses the risks and problems faced of PT X in 2019-2020 with the risk breakdown structure as a resolution to the problems of PT X.